Fish associated with microhabitats of submerged fallen logs in a lake in the Brazilian Amazon - Daniel Olentino; Chiara Lubich; Kedma Yamamoto (Acta Scientiarum. Biological Sciences, 2024)
Microhabitats represent an important factor for fish survival, providing food and shelter, in addition to good temperature conditions and dissolved oxygen levels. One of these temporary microhabitats formed is that of submerged logs, which, due to the flooding of adjacent areas, become available for fish. In this sense, the present study evaluates the composition and structure of fish assemblages associated with submerged logs on the banks of an Amazonian lake and identified the diversity of species according to the hydrological period. Field work was carried out on the banks of Tupé lake, in the lower Negro River, using scoop nets. The sampling was carried out in an area which measured 16 m² (4 m x 4 m) and, within this area, the effort was standardized with the presence of three researchers fishing for approximately one hour in each of the sampling sites. The capture of the fish was carried out with the aid of hand nets (“puçá” and “rapiché”) and sieve. Absolute abundance (N), richness (S), Shannon-Wiener diversity index (H'), Berger Parker dominance (d) and equitability (E) were analyzed. Analysis of variance (p <0.05) was used to verify the temporal variation. A total of 631 specimens were captured, which were distributed in eight families and 25 species, with the orders of Characiformes (67.8%) and Cyprinodontiformes (22.8%) predominating. In the high water period, the highest values of numerical abundance and dominance were observed, while in the low water period, the highest values of species diversity, richness and equitability were found. Therefore, the results presented here can serve as a basis for fisheries management, as well as for conservation measures in these environments that help to maintain fish assemblages.